Cover Image, Volume 29, Issue 5. (May 2016) - Park, Jae Mo; Spielman, Daniel M.; Josan, Sonal; Jang, Taichang; Merchant, Milton; Hurd, Ralph E.; Mayer, Dirk; Recht, Lawrence D.
Abstract : The cover image, by Jae Mo Park et al., is based on the Research Article Hyperpolarized 13 C‐lactate to 13 C‐bicarbonate ratio as a biomarker for monitoring the acute response of anti‐vascular endothelial growth factor (anti‐VEGF) treatment, DOI:10.1002/nbm.3509 .